Transcriptome and Comparative Chloroplast Genome Analysis of Vincetoxicum versicolor: Insights Into Molecular Evolution and Phylogenetic Implication - Yu, Xiaolei; Wang, Wenxiu; Yang, Hongxia; Zhang, Xiaoying; Wang, Dan; Tian, Xiaoxuan (Frontiers in Genetics, 2021)
Vincetoxicum versicolor (Bunge) Decne is the original plant species of Chinese herbal medicine Cynanchi Atrati Radix et Rhizoma. The lack of information on its transcriptome and chloroplast genome hinders the evolution and taxonomic studies of V. versicolor. Here, the transcriptome and chloroplast genome of V. versicolor were assembled and functionally annotated. Moreover, the comparative chloroplast genome analysis was conducted between Vincetoxicum and Cynanchum species. A total of 49,801 transcripts were generated, and 20,943 unigenes were obtained from V. versicolor. 1,032 unigenes from V. versicolor were classified into 73 functional transcription factor families. The bHLH and AP2/ERF transcription factors were significantly abundant and were suggested to be paid attention to the ecological adaptation studies of V. versicolor. The chloroplast genomes of Vincetoxicum and Cynanchum exhibited a typical quadripartite structure with highly conserved gene order and gene content. They shared an analogous codon bias pattern that the codons of protein-coding genes prefer ending with A/U. Natural selection pressure predominantly influenced chloroplast genes. RNA-sequencing (RNA-Seq) revealed an editing event restoring the start codon of ndhD in V. versicolor, whereas mutation in C. auriculatum had corrected the start codon of ndhD at the genome level after the interspecific differentiation in Cynanchum. Phylogenetic trees constructed with protein-coding genes supported the opinion that Vincetoxicum and Cynanchum were two distinct genera.